Studies of the flock mating performance of Booroola merino crossbred ram lambs, and the foot "conditions" in Booroola merino crossbreds and Perendale sheep grazed on hill country : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science in Animal Science at Massey University - Alwan, Mohammed Taha (Massey University, 1983)
Two studies using the Booroola Merino crossbred animals were conducted. In the first, the flock mating performance of Booroola Merino-Romney crossbred ram lambs mated to Perendale ewes was examined. The second study comprised observations on the incidence of foot "conditions" in young Booroola Merino crossbreds and Perendale sheep grazed on hill country. MATING PERFORMANCE Eighteen Booroola Merino x Romney ram lam's (6 control, 12 mating group) were selected according to weaning weight, fleece characteristics and general body condition. Nine ram lambs were exposed to ewes prior to mating for two weeks (trained) and nine kept separate from any ewes (untrained). The ram lambs of the mating group (6 trained, 6 untrained) were allocated to six groups of ewes which were "single-sire" mated. Groups 1, 2, 3, 4 comprised 140 ewes each and Groups 5 and 6 comprised 100 e'\.;res each. The ram lambs were changed after eight, eight, seven and seven days of mating, Periods P1, P2, P3 and P4 respectively, and a total of 12 "single-sire" mating groups generated. All ram lambs produced a satisfactory semen sample before joining with the flocks. Mating commenced on 30 March 1981. The flock mating performance of each ram lamb was assessed by recording the percentage of ewes raddled, percentage of ewes returning to service, percentage of pregnant ewes, percentage of ewes lambing, docking rate and weaning rate. Differences among each of these parameters were attributed to various factors. Trained and untrained ram lambs were similar in most of the observed parameters of flock mating performance. There were no differences between individual ram lambs within each sire-group (trained or untrained) in mating performance. There were differences in the percentage of ewes raddled between first and second oestrous cycle of mating. Live weights of the ram lambs were measured from weaning (December 1980) until the end of the trial (December 1981), at weekly intervals during the mating periods and at monthly intervals during the post-mating and post-shearing periods. There was little loss in the mean live weight of the mating group ram lambs after P1. Overall the live weights of both groups increased consistently throughout the trial. Semen samples (collected by electro-ejaculation) from the ram lambs of the mating group were microscopically examined for general motility after each mating period at least for three days. Recovery from mating exhaustion occurred four and six days after P1 and Pz respectively, while three and two days were required after P3 and P4 respectively. Semen samples were also collected on two occasions from the rams (only 15) as two-tooths and examined for general motility, sperm concentration and percentage of live sperm. There were no differences in semen characteristics between rams of the mated and control groups. The two-tooth rams were also subjected individually and randomly on three occasions to pen-libido tests, each with two oestrous ewes. Mating ability was assessed by recording the number of mounts attempted on the oestrous ewes, the number of services, the reaction time to mount (in seconds) and the reaction time to service. There were no differences between the mating and control groups in the number of mounts and number of services performed on each occasion of the libido test. Significant differences were found between both groups in reaction time to mount and in reaction time to service but only at the first libido test. It was concluded that the Booroola Merino x Romney ram lambs had achieved satisfactory levels of flock mating performance under the conditions of the trial. No adverse effects of mating on the post-mating body development of the ram lamb could be detected. Semen quality from the ram lambs deteriorated during mating but recovered shortly after mating. The use of ram lambs as sires had no adverse effects on their semen characteristics and libido performance at the two-tooth age. FOOT "CONDITIONS" The incidence of abnormal foot shape, foot scald and footrot was observed in Perendale and Booroola Merino crossbreds. The animals were generated in 1980 and 1981. Observations on foot "conditions" were made at the lamb, hogget and two-tooth ages for animals born in 1980, and at the lamb and hogget ages for those born in 1981. A scoring system was used to rank the various foot "conditions" (shape; scald; footrot) which were assessed separately. Booroola Merino crossbreds showed significantly a higher incidence of abnormal foot shape, foot scald and footrot than did Perendale sheep. Significant differences in foot "conditions" were also found between (Booroola x Romney) x Perendale and Booroola x Romney sheep. Sires of the progeny generated in 1980 and 1981 provided a major source for the variation in the incidence of these foot "conditions". Estimates of heritability of each of the observed foot "conditions" were calculated at different ages (lamb, hogget and two-tooth). Sex of the lamb caused significant effects on the incidence of abnormal foot shape and foot scald between ram lambs and ewe lambs, but not on the incidence of footrot. Differences in the incidence of abnormal foot shape and foot scald occurred between 1980- and 1981-born sheep. These differences were attributed partly to the particular climatic conditions in each year (notably the annual rainfall). It was concluded that under environmental conditions similar to that of the present trial, long-term selection programmes could be applied to enhance the natural resistance of sheep against foot diseases.
Keywords: Merino sheep; Perendale sheep; Footrot in sheep; Sheep reproduction